2012
DOI: 10.4314/evj.v16i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate of clinical bovine mastitis in selected smallholder dairy farms in Gondar town, Ethiopia

Abstract: A study was conducted in Gondar town in six selected smallholder farms from August 2005 to January 2006 for six months to measure incidence rate of clinical bovine mastitis. Monitoring was performed by animal attendants of each farm after training and supervision of the monitoring activities and collection of data was performed by the researchers. Farmers identified cases of clinical mastitis on the basis of abnormalities in milk, in the udder or systemic abnormalities of the cow. A second or third case of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
2
2
Order By: Relevance
“…This nding corresponds with [20], who found that breed had a signi cant effect on the prevalence of mastitis. The results were comparable to previous studies [21,12] Mastitis prevalence among breeds, on the other hand, may indicate variations in management rather than an actual genetic difference [9].…”
Section: Discussionsupporting
confidence: 88%
“…This nding corresponds with [20], who found that breed had a signi cant effect on the prevalence of mastitis. The results were comparable to previous studies [21,12] Mastitis prevalence among breeds, on the other hand, may indicate variations in management rather than an actual genetic difference [9].…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, the current incidence rate is much higher than a previous nding of 21.26 cases per 100 cow years at risk in Gondar town in northern Ethiopia [25]. The higher incidence rate in the present study may be related to a longer observation period of the cows and a larger sample size compared to a sixmonth follow-up by Almaw and his co-researchers.…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of sub-clinical mastitis (66.7%) was found to be higher compared to studies done in Ethiopia (52.3% -34.9%) [15,16], Kenya (59.5%) [17], Egypt (40%) [18], Uganda (37%) [19] and Tanzania (53.2%) [20]. The results were comparable to the ones found in Ethiopia [21] which found a prevalence of 61.1%. However, the results were lower than those reported in Nigeria (85.5%) [22], Ethiopia (72.7%) [23].…”
Section: Discussionsupporting
confidence: 44%